1967
DOI: 10.1080/0013188670090307
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Practice in the Education of Teachers

Abstract: COLLEGES of Education have retained, throughout their years of development, a system of concurrent education whereby students combine theoretical work in college with periods of practice in schools. The overall arrangements regarding length of practice are well known: the college studied in this research was typical in having fifteen weeks of practice distributed between each of the three years of the course. Students were on 'school practice' for two weeks in the autumn and three weeks in the summer terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
2

Year Published

1969
1969
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 1 publication
1
10
2
Order By: Relevance
“…Two participants chose political metaphors to describe their metaphor of literacy. (Authors, 2005;Shipman, 1967;Zeichner & Tabachnick, 1981). Therefore, our findings were incongruous with previous research since 44% of our preservice teachers seemed open to program ideas and related their metaphors to course content.…”
Section: Nurturing Four Individuals Selected Words To Describe Theircontrasting
confidence: 56%
See 1 more Smart Citation
“…Two participants chose political metaphors to describe their metaphor of literacy. (Authors, 2005;Shipman, 1967;Zeichner & Tabachnick, 1981). Therefore, our findings were incongruous with previous research since 44% of our preservice teachers seemed open to program ideas and related their metaphors to course content.…”
Section: Nurturing Four Individuals Selected Words To Describe Theircontrasting
confidence: 56%
“…Zeichner and Tabachnick (1981) looked at the literature regarding the effects of teacher education programs and learned that university preparation has minimal impact. Shipman (1967) concluded there was a lack of college influence; the pre-service teachers possibly aligned their opinions with the prevailing university culture in a veneer-type layer to insulate themselves, but there was no real change. Authors (2005) found the persistence of ideas that beginning teachers bring to their university preparation and those beliefs extend into actual classroom practice.…”
Section: Theoretical Framework Teaching Beliefsmentioning
confidence: 99%
“…Shipman (1966Shipman ( , 1967 has reported similar findings, but he suggests that the changes that occur during training are really only superficial. Students, Shipman says, employ 'impression management' to insulate them from college influence and to retain the attitudes they entered with, attitudes more in line with those found in schools than those the training institution would like to transmit (Shipman, 1967, p. 209).…”
Section: Educational Research Volume 21 Numbersupporting
confidence: 57%
“…Research has concentrated on one particular age level (Steele, 1958); or with a particular issue such as corporal punishment (Kissack, 1958); or with an examination of attitudes towards educational beliefs and practices, without specifying particular age levels (Butcher, 1965;Evans, 1967;Herbert and Turnbull, 1963;Dickson, 1965;Mclntyre and Morrison, 1967;Finlayson and Cohen, 1967;Shipman, 1967). There is, in these studies, a general consensus that students preparing to teach younger children tend to hold a more liberal, child-centred view of the role than students preparing to teach older children, but there have been no investigations into the degree and nature of differences between primary and secondary teacher role conceptions.…”
Section: R Gibson Cambridge Institute Of Educationmentioning
confidence: 98%